PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN PESERTA DIDIK MELALUI MEDIA KARTU HURUF PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS II SD INPRES LILI KABUPATEN KUPANG: Penelitian Tindakan Kelas - Lodo Nawa, Hesty Octaviani; Markus Sampe; Kurniayu T. R. A. Ratu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Research results by Hesty Octaviani Lodo Nawa Nim 2101140069 with the title Improving Students' Beginning Reading Skills Through Letter Card Media in Indonesian Language Subjects in Grade 2 of UPTD SD Inpres Lili, Kupang Regency. With the formulation of the problem: